2022
DOI: 10.5125/jkaoms.2022.48.4.192
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and prognostic factors in oral tongue cancer: a 20-year retrospective study at the National Cancer Center, South Korea

Abstract: Objectives This study aimed to analyze the treatment outcomes and to evaluate the clinicopathological prognostic factors of oral tongue cancer. Patients and Methods We retrospectively analyzed treatment results and prognostic factors in 205 patients with oral tongue squamous cell carcinoma who were admitted to the National Cancer Center, South Korea, between January 2001 and December 2020. The patients were treated with surgery and postoperative, definitive radiotherapy (RT) or chemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Several articles also observed same effect, showing that pathologic differentiation was associated with OS 13 and DFS 41,43 in oral cancer. Kim et al 25 . have reported pathologic differentiation as an independent factor for OS in patients of oral tongue cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several articles also observed same effect, showing that pathologic differentiation was associated with OS 13 and DFS 41,43 in oral cancer. Kim et al 25 . have reported pathologic differentiation as an independent factor for OS in patients of oral tongue cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles also observed same effect, showing that pathologic differentiation was associated with OS 13 and DFS 41,43 in oral cancer. Kim et al 25 have reported pathologic differentiation as an independent factor for OS in patients of oral tongue cancer. Thus, histological grade may be a potential factor indicating the need for postoperative adjuvant therapy, and the patients with a lower degree of differentiation may need more stringent follow-up after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, PNI and LVI, which proved to possess a high discriminatory potential, have been reported to be present in approximately 20%-40% and 10%-30% of the OSCC cases, respectively. 6,[21][22][23] This implies that in more than half of the OSCC cases, an additional descriptor of tumor aggressiveness would be of utmost importance, and that this descriptor should ideally be interpreted on a continuous scale, as converting inherently non-categorical into categorical data will potentially result in loss of information through a priori assumptions. 24 The approach to diagnosing and confirming cancer through microscopic examination of resected tissue has remained largely unchanged since the late 1800s.…”
Section: Introductionmentioning
confidence: 99%
“…While Kim et al. emphasized the excellent survival of appropriately treated TSCCs according to statistical analyses of the Surveillance, Epidemiology, and End Results (SEER) database, other recent reports have shown a modest 5‐year disease‐free survival of 63% across all T‐categories 5,6 . Moreover, tumor recurrence occurs in up to 30% of early stage TSCCs 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation